Pengembangan Media Pembelajaran Augmneted Reality Materi Prisma Dalam Meningkatkan Hasil Belajar Peserta Didik - Majid, Abdul; Amrullah; Novitasari, Dwi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to develop Augmented Reality learning media on prism material in improving the learning outcomes of class VIII students of MTsN 2 Mataram. This study is a research and development (R&D) with a 4D model. The sample of this study was 32 class VIII A students of MTsN 2 Mataram. In the design stage, AR media was designed using the Assemblr Edu platform, then the AR content was implemented in LKPD. In the development stage, two small-scale trials were conducted to obtain data on the practicality and effectiveness of the media. The research instruments used were questionnaires and learning outcome test questions. Data analysis techniques were used to determine the level of validity, practicality, and effectiveness of the developed learning media. The results of the study show that the AR media developed (1) is valid with a validity score of 0.78 and a valid category using the Aiken V formula, (2) is practical with a percentage of 86.9% and a very practical category using the practicality percentage, (3) is effective with a classical completion percentage of 81.25% in a very high category so that the Augmented Reality learning media developed is effective for improving learning outcomes.